Editorial - Evans, Ken (European Journal for Qualitative Research in Psychotherapy, 2012)
In each of the five articles in this December 2012 issue of the research journal relationship features strongly in one way or another. This was not by design but was noticed only following the peer review of the final article chosen for publication. This field emergent occurrence likely reflects the significant contemporary interest in the co-created nature of clinical prac- tice and relational centred research. The articles were sent from Sweden, the United Kingdom, Malta and France.